Role of the vaginal microbiome in miscarriage: exploring the relationship - Saadaoui, Marwa; Singh, Parul; Ortashi, Osman; Al Khodor, Souhaila (Frontiers in Cellular and Infection Microbiology, 2023)
Miscarriage is a devastating pregnancy loss that affects many women worldwide. It is characterized as a spontaneous miscarriage that occurs before 20 weeks of gestation which affects more than 25% of pregnancies. While the causes of miscarriage are complex and multifactorial, recent research has suggested a potential role of the vaginal microbiota. The vaginal microbiome is a dynamic ecosystem of microbes that are essential for preserving vaginal health and avoiding infections. Vaginal dysbiosis has been accompanied with numerous adverse pregnancy complications, such as preterm birth. However, the effect of the vaginal microbiome in miscarriage is not fully understood. This review aims to investigate the link between vaginal microbiota and miscarriage. Also, we investigate the various mechanisms through which the vaginal microbiota may affect miscarriage. Additionally, we examine the implications of these research findings, specifically the possibility of vaginal microbiome screening and targeted interventions to prevent miscarriage.